2009
DOI: 10.1111/j.1744-7429.2009.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Loop: Why Research Rarely Reaches Policy Makers and the Public and What Can be Done

Abstract: Most of the world's population that derives their livelihoods or part of their livelihoods from forests are out of the information loop. Exclusion of public users of natural resources from access to scientific research results is not an oversight; it is a systemic problem that has costly ramifications for conservation and development. Results of a survey of 268 researchers from 29 countries indicate that institutional incentives support the linear, top-down communication of results through peer-reviewed journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 48 publications
(75 reference statements)
2
135
0
3
Order By: Relevance
“…However this literature is not systematically accessible (Knight et al, 2008) and it can be difficult to assess the reliability of the data (Parr & Chown, 2003). As a result, researchers mainly use the peer-reviewed literature and rarely seek out the literature in which practitioners communicate their own work (Shanley & López, 2009). The fact that researchers do not use the information produced by practitioners may contribute to the lack of relevance of their research, and therefore more recognition of, but also more access to, the science led by practitioners is necessary to facilitate its uptake by researchers, who could in turn develop research projects relevant to practitioners' needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However this literature is not systematically accessible (Knight et al, 2008) and it can be difficult to assess the reliability of the data (Parr & Chown, 2003). As a result, researchers mainly use the peer-reviewed literature and rarely seek out the literature in which practitioners communicate their own work (Shanley & López, 2009). The fact that researchers do not use the information produced by practitioners may contribute to the lack of relevance of their research, and therefore more recognition of, but also more access to, the science led by practitioners is necessary to facilitate its uptake by researchers, who could in turn develop research projects relevant to practitioners' needs.…”
Section: Discussionmentioning
confidence: 99%
“…We also examine whether, and if so why, researchers and practitioners in developing countries consider a journal's Impact Factor (Web of Science, 2014) in deciding which scientific research to use in their work. The Impact Factor may be irrelevant in determining whether published research has a conservation impact (Shanley & López, 2009) but there is pressure on researchers to publish their work in high-impact journals (Milner-Gulland et al, 2012). Finally, we consider the responses of practitioners when asked what would make the peer-reviewed literature more useful for them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…stakeholders, the company, the community) has been observed in other areas of NIS control (e.g. Donlan et al 2003, Gardener et al 2010, Shanley and López 2009, and represents another problem to be solved in order to achieve effective control programs of the golden mussel. …”
Section: Resultsmentioning
confidence: 99%
“…A survey in 2009 of 268 ecological scientists found that although 43 per cent reported that scientific papers were the most important factor in assessing their academic performance, only 15 per cent believed that peerreviewed journals were effective in promoting conservation (Shanley & Lopez, 2009 This situation is hopefully set to change soon as many academic journals have or are moving from a model where authors publish for free and readers pay for access to a model where authors will pay a fee to publish and access will be free. This change will be a huge improvement in terms of access to the academic literature, but of course the downside is that it will create a new barrier to publication by practitioners, because the fees for publication are likely to be substantial.…”
Section: Introductionmentioning
confidence: 99%